Short- and long-term prognosis of acute critically ill patients with systemic rheumatic diseases: A retrospective multicentre study. Issue 35 (3rd September 2021) - Chabert, Paul; Danjou, William; Mezidi, Mehdi; Berthiller, Julien; Bestion, Audrey; Fred, Abla-Akpene; Guerin, Claude; Argaud, Laurent; Piriou, Vincent; Bonnefoy-Cudraz, Eric; Lehot, Jean-Jacques; Fellahi, Jean-Luc; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Patients with systemic rheumatic disease (SRD) share the risks of multi-organ flare-up, cardiovascular diseases, and immunosuppression. Such situations can lead to an acute critical illness. The present study describes the clinical features of SRD patients admitted to the intensive care unit (ICU) and their short- and long- term mortality. We performed a multicentre retrospective study in 10 French ICU in Lyon, France. Inclusion criteria were SRD diagnosis and admission for an acute organ failure. The primary endpoint was ICU mortality. A total of 271 patients were included. SRD included systemic lupus erythematosus (23.2% of included patients), vasculitis (10.7%), systemic sclerosis (10.7%), idiopathic inflammatory myopathy (6.3%), and other connective tissue disorders (rheumatoid arthritis, Sjögren and Sharp syndromes; 50.9%). Initial organ failure(s) were shock (43.5% of included patients), acute kidney injury (30.5%), and acute respiratory failure (23.2%). The cause(s) of ICU admission included sepsis (61.6%), cardiovascular events (33.9%), SRD-flare up (32.8%), and decompensations related to comorbidities (28%). The ICU mortality reached 14.3%. The factors associated with ICU mortality were chronic cardiac failure, invasive ventilation and admission in ICU for another reason than sepsis or SRD flare-up. The median follow-up after ICU discharge was 33.6 months. During follow-up, 109 patients died. The factors associated with long-term mortality included age, Charlson comorbidity index, and ICU admission for sepsis or SRD flare-up. The ICU mortality of patients with SRD was low. Sepsis was the first cause of admission. Cardiovascular events and comorbidities negatively impacted ICU mortality. Admission for sepsis or SRD flare-up exerted a negative effect on the long-term outcome.